Diffraction from relief gratings on a biomimetic elastomer cast - Guerrero, Raphael A (Archīum Ateneo, 2010)
Biomimetic optical elements combine the optimized designs of nature with the versatility of materials engineering. We employ a beetle carapace as the template for fabricating relief gratings on an elastomer substrate. Biological surface features are successfully replicated by a direct casting procedure. Far-field diffraction effects are discussed in terms of the Fraunhofer approximation in Fourier space.